Teknik Pembebasan Emosi - Spiritual dan Perubahan Siptom Fisiologis Penderita Gangguan Fobia Kucing - Alfin Ruzhendi; Nur Rahmanto Heryana (Universitas Islam Indonesia, 2010)
The research aims at determining whether Spiritual Emotional Freedom Technique (SEFT) is effective to decrease the symptoms of cat phobia (Ailurofobia). Metode yang digunakan dalam penelitian ini adalah metode eksperimen. The One Group Pre-Test and Post-Test Design of experiment was applied. The Phobia Scale was used. The result show that there was effect of SEFT at cat phobia's symptom. The psysiological symptoms decreased by the change of perception to the cat. Biologically, SEFT has change the prefrontal cortex that accept the suggestion exactly. Subjecb've perception changed psychologically, followed by decreased of physiological symptoms.Keyword : Cat phobia (Ailurofobia), Spiritual Emotional Freedom Technique (SEFT)